2010
DOI: 10.1002/app.33284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boric acid and heat treatment for the formation of poly(vinyl alcohol)/iodine complex films iodinated at solution before casting

Abstract: This study examined the role of boric acid and the effect of heat treatment on PVA-iodine polarizing films prepared in the solution state before casting (IBC) of PVA/iodine/boric acid films. The films were prepared by casting aqueous solutions of 10 wt % poly(vinyl alcohol) (PVA) containing boric acid with 0, 0.1, 0.3, and 0.5 mol/l of I 2 /KI aqueous solution, and I 2 /KI(1 : 2) with 5 wt % of PVA. The effect of boric acid and heat treatment on the durability of the IBC PVA polarizing sheet films was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…High amounts of solvents such as acetone, DMF, methanol, ethanol, pyridine, or formic acid, will destroy the complex and the color will fade. Shin et al [173,174] reported the use of boric acid treatment to form I 2 PVA polarizing film characterized by its transmittance and polarization degree. The acid promoted the formation of iodide species I 3¯ and I 5¯, and improved the durability of the film under heat and humidity.…”
Section: Iodine-proteinic Fiber Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…High amounts of solvents such as acetone, DMF, methanol, ethanol, pyridine, or formic acid, will destroy the complex and the color will fade. Shin et al [173,174] reported the use of boric acid treatment to form I 2 PVA polarizing film characterized by its transmittance and polarization degree. The acid promoted the formation of iodide species I 3¯ and I 5¯, and improved the durability of the film under heat and humidity.…”
Section: Iodine-proteinic Fiber Complexesmentioning
confidence: 99%
“…The acid promoted the formation of iodide species I 3¯ and I 5¯, and improved the durability of the film under heat and humidity. Boric acid seemed to disfavor the crystallization, inducing the formation of an amorphous region [173]. In fact, Woo et al [172] worked on the effect of boric acid on the crystallinity and the drawability of the I 2 PVA films made by iodinating the PVA solution before and after casting its solution, BC and AC, respectively.…”
Section: Iodine-proteinic Fiber Complexesmentioning
confidence: 99%
“…The five absorption peaks that appeared at ∼ 200, 310, 370, 480, and 650 nm were assigned to I − , I 3 − , I 2 ·I 3 − , I 3 − , and I 5 − ions, respectively. The first three peaks were confirmed by the experiment for PVA dissolved in the I 2 /KI solution, and the last two peaks were attributed to the formation of the PVA/iodine complexes 6, 13. The strength of the first three peaks was greater than the last two peaks, indicating that mostly the iodine ions (I − , I 3 − , and I 2 ·I 3 − ) existed in the PVA films, but a few PVA/iodine complex ions (PVA‐I 3 − and PVA‐I 5 − ) were also present.…”
Section: Resultsmentioning
confidence: 67%
“…In our previous studies, we have estimated the effect of boric acid on durability of PVA–iodine polarizing sheet film12, 13 in the iodination at solution before casting (IBC); boric acid combined with the PVA chain to form intramolecular crosslinking segments that were regarded as a defect in the crystal, which decreased the melting temperature of PVA. The formation of I 3 − and I 5 − increased with increasing boric acid content in IBC state.…”
Section: Introductionmentioning
confidence: 99%
“…Boric acid forms crosslinked bonding in PVA, and it stabilizes PVA–polyiodine complexes in the polymer. The effects of boric acid on PVA–polyiodine complexes and the reactions have been studied, and a mechanism has been proposed …”
Section: Introductionmentioning
confidence: 99%